Stretchable Thermoelectric Generators Based on Bulk Bi2Te3 and Liquid Metals - Renheng Wang; Mingli Wu; Dongting Jiang; Hao Liang; Wei He; Yiling Sun; Zhengfang Qian (Advanced Electronic Materials, 2023)
Abstract Flexible energy‐generating electronics have attracted great interest. Generally, such devices can be classified into three categories: energy storage, energy harvesting, and wireless charging. In this work, a flexible thermoelectric generator (TEG) for energy harvesting is fabricated. Bi2Te3 ingots are used as thermoelectric legs. To introduce flexibility, liquid metals and elastomers are utilized as the interconnects and encapsulation, respectively. The as‐fabricated device exhibits an output density of 34.5 µW cm−2 over a temperature difference of 25 °C. The device exhibits promising robustness under mechanical stretching, as the fracture limits reach 100%. The device is tested on the human body, and it delivers an instantaneous output of 75.2 mV. Therefore, the as‐fabricated TEG is suitable for human wearable electronic applications.